MINERAL LAW AND THE DOCTRINE OF RIGHTS: A MICROSCOPE OF MAGNIFICATION? - PJ Badenhorst (Obiter, 2022)
The doctrine of rights has become part of private law jurisprudence. In this article the application of the doctrine in two decisions dealing with surface support in mineral law is examined. It is argued that the decision of Kriegler J in Elektrisiteitsvoorsieningskommissie v Fourie, namely, that the right to surface support is an entitlement, is more correct than Anglo Operations Ltd v Sandhurst Estates (Pty) Ltd in which it was decided that the right to surface support is a competence. It is submitted that depending on the legal location of the entitlement in the relationship between owner and miner of land one may simply refer to either an owner’s entitlement to surface support or a miner’s entitlement to undertake opencast-cast mining.